Effects of initial stresses on guided waves in unidirectional plates - Zhang, X.M.; Yu, J.G. (Archives of Mechanics, 2013)
The guided wave propagation in unidirectional plates under gravity, homogeneous initial stress in the thickness direction and inhomogeneous initial stress in the wave propagating direction is investigated in this paper based on the theory of mechanics of incremental deformations. The Legendre orthogonal polynomial series expansion method is used to solve the coupled wave equation. Two different wave propagating directions, the fiber orientation and the vertical fiber orientation, are discussed respectively. The effects of the initial stresses on the Lamb-like wave and shear-horizontal (SH) wave are respectively investigated. The effects of the initial stresses on the dispersion curves and on the displacement and stress distributions are discussed.